Framing Media Atas Pemberitaan Sertifikasi Dai - Abd Munib (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Religious messages conveyed by extremist preachers have the opportunity to move the congregation to anti-tolerant actions that can threaten the nation and state. Based on this, the Indonesian Ulema Council (MUI) sees the need for a standardization policy in order to create enlightening lecturers. This incident did not escape the media spotlight. The media even had their own characteristics in filming the standard of dai. The news of dai's certification did not escape the media spotlight. This scientific work aims to reveal the online media framing of Tempo.co, Medcom.id, and BBC.com for reporting on dai's certification. The theory used in this research is the Zhong Dang Pan and Gerald M. Kosicki's framing theory which classifies the structural news text on four dimensions as a framing device, namely syntax, script, thematic and rhetoric. This study uses a qualitative descriptive research method where the data will be presented in the form of a description of the results of the analysis of the news on certification from Tempo.co, Medcom.id, and BBC.com. The framing of the news carried out by the three online media shows a difference. Tempo.co framed that dai certification was seen as an important policy that MUI had to take in order to create enlightenment. As for Medcom.id, in framing MUI's policy on standardization of ulama, it emphasizes and awaits support from religious organizations such as NU and Muhammadiyah. Meanwhile, BBC.com is more concerned about the benchmarks that will be used by MUI in dai certification